PENGARUH STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM PADA PT. RAMAYANA LESTARI SENTOSA, TBK PERIODE 2014-2023 - Ahmad, Farah Aulia; Supriatna, Agus (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to determine the partial and simultaneous effects of Capital Structure (Debt to Equity Ratio) and Firm Size on Stock Prices at PT Ramayana Lestari Sentosa Tbk from 2014 to 2023. The method used is quantitative. The data source in this study is secondary data obtained from annual financial reports for the period 2014-2023. Data analysis was performed using SPSS version 29 with descriptive statistical analysis, classical assumption tests, linear regression tests, t-tests and F-tests, as well as coefficient of determination tests. The results showed that Capital Structure (Debt to Equity Ratio) did not have a significant effect on Stock Price, with a tcount < ttable or 0.572 < 2.365 and a significance value of 0.585 > 0.05. and Firm Size did not have a significant effect on Stock Price, with tcount < ttable or 0.505 < 2.365 and a significance value of 0.629 > 0.05. Simultaneously, both variables do not have a significant effect on Stock Price with Fcount < Ftable or 0.249 < 4.74, and a significance value of 0.786 > 0.05.